1H NMR and PCA-based analysis revealed variety dependent changes in phenolic contents of apple fruit after drying. (15th April 2017) - Francini, Alessandra; Romeo, Stefania; Cifelli, Mario; Gori, Daniele; Domenici, Valentina; Sebastiani, Luca
Highlights: Effects of variety and drying process on apple's polyphenolic content were investigated. Antioxidant capacity and total polyphenol content were determined on dry and fresh apples. 1 H NMR spectral analysis combined with PCA multivariate approach were used to characterize apples. Ancient underutilized apples showed greater polyphenol contents and antioxidant activity than cultivated apples. The antioxidant capacity of the ancient underutilized apples remain higher than reference apple after drying. Abstract: Dry and fresh apples have been studied monitoring their polyphenolic profiles through 1 H NMR, antioxidant capacity and total polyphenol content. Six ancient and underutilized apple varieties (Mantovana, Mora, Nesta, Cipolla, Ruggina, Sassola) and a commercial one (Golden Delicious) were dried with an air-drying system at 45 °C for 19 h. Although some of their polyphenol constituents were lost during drying, the antioxidant capacity of some apple varieties remained higher compared to Golden Delicious. This result is very important for ancient and underutilized varieties that are not consumed on large scale as fresh product since they have low attractiveness, due to their ugly appearance. Combining quantitative NMR spectroscopy with principal component analysis we have identified and quantified several polyphenols (such as catechin, epicathechin, and chlorogenic acid) that are important to establish the nutraceutical value of the different investigated apple varieties.